The Influence of Internal Control System, Internal Audit, and GCG on Banking Financial Performance - Esti Mugi Lestari; Eko Giyartiningrum (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this research is to analyze the impact of internal control systems, internal audits, and GCG on the financial performance of banks listed on the Indonesia Stock Exchange (IDX). A quantitative research method using multiple linear regression was used with 46 banks from a total of 138 observations. The data used are secondary data obtained from published annual reports of banks. The dependent variable in this research is banking financial performance as measured by Return on Equity (ROE). The variables of internal control systems, internal audits, and good corporate governance (GCG) are the independent variables in this research. The GCG variable is proxied by independent commissioners, institutional ownership, the board of directors, managerial ownership, the audit committee, and the activities of the board of commissioners. The research results show that only the activities of the board of commissioners have a significant effect on improving bank financial performance. Thus, other factors need to be further studied to understand their impact on overall banking financial performance.